HIGH-TECH PAIN MANAGEMENT: REGIONAL ANESTHESIA AND PERIPHERAL NERVE BLOCKS - Yusupova Baxtigul Djumabayevna (Modern American Journals, 2025)
Regional anesthesia is becoming a key component of modern perioperative pain management, particularly within Enhanced Recovery After Surgery (ERAS) protocols. This article provides an in-depth review of the pharmacological foundations, clinical applications, and technological advancements of regional anesthesia, with an emphasis on peripheral nerve blocks. The mechanisms of local anesthetics, differential nerve fiber blockade, and comparative characteristics of spinal, epidural, and peripheral techniques are summarized. Special attention is given to ultrasound guidance as a transformative technology that improves precision, safety, and drug deposition efficiency. The clinical significance of peripheral nerve blocks is analyzed in the context of multimodal analgesia, opioid reduction, early mobilization, and improved postoperative recovery. Future prospects include the integration of artificial intelligence and Big Data to enhance nerve identification, optimize anesthetic distribution, and predict postoperative pain outcomes. Regional anesthesia is presented as a critical tool for improving patient safety, accelerating rehabilitation, and elevating overall perioperative care quality.
Keywords: Regional anesthesia, peripheral nerve block, ultrasound guidance, multimodal analgesia, ERAS, local anesthetics, differential blockade, postoperative pain, opioid-sparing strategies.